Analisis SWOT Pemilihan Material Dinding Bata Merah dan Bata Ringan di Penajam Paser Utara - Hendriyani, Irna; Marini, Andi; Intan Putri, Nur (Borneo Engineering : Jurnal Teknik Sipil, 2018)
Infrastructure contruction has expanded in Penajam Paser Utara brought the effect of wall materials. Nowdays, Building construction with light brick preferably as an alternative than red brick it self. The aim of this research is to conduct SWOT Analysis between light brick and red brick in construction build in Penajam Paser Utara. According to question form that was spread in to local government has shown the results, The red brick sited in forth coordinate (quadrant) compare with light brick in second quadrant. This quadrant position provide using light bricks preferably were been selected than common red brick